Comparison of patient-reported outcomes of treatment with low- and intermediate molecular weight hyaluronic acid in Japanese patients with symptomatic knee osteoarthritis: A prospective, randomized, single-blind trial - Takeshi Mochizuki; Katsunori Ikari; Koichiro Yano; Ken Okazaki (Elsevier, 2020)
Objectives: The objective of this study was to compare the clinical outcomes of treatment with low- or intermediate-molecular-weight hyaluronic acid (HA) in patients with knee osteoarthritis (OA). Methods: In total, 59 patients with OA who fulfilled the criteria of the American College of Rheumatology for OA were enrolled. Patients were randomly assigned in a 1:1 ratio to the low- or intermediate-molecular-weight HA group. An intraarticular injection of HA into the knee joint was performed five times per week. The visual analog scale for pain (pain VAS) and Japanese Knee Osteoarthritis Measure (JKOM) score were analyzed at baseline and week 6 to assess the outcomes. Results: Pain VAS and JKOM score were significantly improved in both groups. At follow-up, there were no significant between-group differences in pain VAS or total JKOM score. Moreover, reduction in pain VAS and JKOM score was not significantly different between the two groups. Conclusions: Both low- and intermediate-molecular-weight HA have significant efficacy in the first-line treatment of patients with knee OA as indicated by patient-reported outcomes. However, there does not appear to be any difference between the efficacy of low- and intermediate-molecular-weight HA as indicated by the JKOM score. We believe that the results of this study provide important insights into the clinical management of Japanese patients with knee OA.